2005
DOI: 10.1128/aem.71.9.5225-5235.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Extensive Diversity of Ionizing-Radiation-Resistant Bacteria Recovered from Sonoran Desert Soil and Description of Nine New Species of the Genus Deinococcus Obtained from a Single Soil Sample

Abstract: The ionizing-radiation-resistant fractions of two soil bacterial communities were investigated by exposing an arid soil from the Sonoran Desert and a nonarid soil from a Louisiana forest to various doses of ionizing radiation using a 60 Co source. The numbers of surviving bacteria decreased as the dose of gamma radiation to which the soils were exposed increased. Bacterial isolates surviving doses of 30 kGy were recovered from the Sonoran Desert soil, while no isolates were recovered from the nonarid forest so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
211
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(218 citation statements)
references
References 67 publications
7
211
0
Order By: Relevance
“…The majority (74%) of Actinobacteria sequences identified in this study belong to the deepest branch of the phylum, the Rubrobacteridae, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress (Holmes et al, 2000;Rainey et al, 2005). The involvement of Rubrobacteridae in soil aggregate formation and calcite precipitation suggests that they may also be involved in engineering the soil surface structure during biocrust formation (Mummey and Stahl, 2004;Rainey et al, 2005;Mummey et al, 2006;Pellerin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (74%) of Actinobacteria sequences identified in this study belong to the deepest branch of the phylum, the Rubrobacteridae, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress (Holmes et al, 2000;Rainey et al, 2005). The involvement of Rubrobacteridae in soil aggregate formation and calcite precipitation suggests that they may also be involved in engineering the soil surface structure during biocrust formation (Mummey and Stahl, 2004;Rainey et al, 2005;Mummey et al, 2006;Pellerin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The majority (74%) of Actinobacteria sequences identified in this study belong to the deepest branch of the phylum, the Rubrobacteridae, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress (Holmes et al, 2000;Rainey et al, 2005). The involvement of Rubrobacteridae in soil aggregate formation and calcite precipitation suggests that they may also be involved in engineering the soil surface structure during biocrust formation (Mummey and Stahl, 2004;Rainey et al, 2005;Mummey et al, 2006;Pellerin et al, 2009). Filamentous Chloroflexi bacteria have been visualized within sheaths of Microcoleus chthonoplastes in hypersaline microbial mats and co-located with M. vaginatus in biocrusts of a high elevation site in Colorado, but whether the relationship between the two species is symbiotic or antagonistic is not known (Ley et al, 2006;Freeman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because of our interest in radiation-resistant bacteria and the correlation that has been made between desiccation and radiation resistance (Mattimore & Battista, 1996), we have studied bacteria that survive in the desert. Desiccation-and radiation-resistant bacteria have been observed in several genera, including Deinococcus, Rubrobacter, Hymenobacter, Methylobacterium, Kocuria and Kineococcus (Rainey et al, 2005;Phillips et al, 2002). The genus Kineococcus was first created by Yokota et al (1993) with the species Kineococcus aurantiacus, based on a single strain isolated from soil.…”
mentioning
confidence: 99%
“…The pH range (pH 5-10 at intervals of 1 pH unit) for growth was determined in tenfold-diluted marine broth (Difco). In addition, carbohydrate utilization was tested using a defined medium solidified with deionized water-washed agar, as described previously (Rainey et al, 2005). Growth was examined visually on plates incubated at 30 u C for up to 7 days.…”
mentioning
confidence: 99%
“…In our study, the order Gaiellales was only found in galled plant roots (0.09%). In contrast to the root samples, the galled leaf samples had a large proportion of Rubrobacterales belonging to the genus Rubrobacter, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress [ 67,68 ]. This finding is notable as B. dracunculifolia is a pioneer species capable of colonizing the extremely harsh habitats of the mountain top rupestrian grasslands.…”
Section: Echinoides S Suberifaciens S Changbaiensis Smentioning
confidence: 99%